Evolution of Cooperative Models: A Comparative Analysis of Traditional Cooperatives (TC) and New Generation Cooperatives (NGC) - Ibrahim, Riza Andrian; Salih, Yasir; Sidiq, Fahmi (Communication in Research and Publications (CRP), 2023)
Cooperatives as membership-based economic entities have experienced an evolution from the traditional model (TC) to the new generation model (NGC). TC is known for its social orientation and simple structure, but often experiences limited capital and difficulty adapting to modern business dynamics. Responding to these weaknesses, NGC comes with a business model that is more open to external capital, professional management, and full supply chain penetration. Even though it provides significant added value, NGC is faced with challenges in maintaining the social values of cooperation and relationships between members. This article analyzes the comparison between TC and NGC, highlights the advantages and disadvantages of each model, and formulates the future development direction of cooperatives that integrates the positive elements of both models. The results of this research provide a basis for formulating recommendations for cooperative development in the future. It is recommended that cooperatives adopt a flexible business model, combining traditional and modern aspects. The importance of maintaining cooperative social values is in line with increasing efficiency and competitiveness. Efforts are needed to increase member literacy in terms of business management, and cooperatives need to build strategic partnerships with external parties to support growth and innovation. It is hoped that the implementation of these recommendations can lead cooperatives towards a sustainable future and provide maximum benefits for their members.